2019
DOI: 10.1096/fj.201900436rr
|View full text |Cite
|
Sign up to set email alerts
|

The role of EGFR signaling in age‐related osteoporosis in mouse cortical bone

Abstract: So far, there has been no effective cure for osteoporotic cortical bone, the most significant change in long bone structure during aging and the main cause of bone fragility fractures, because its underlying molecular and cellular mechanisms remain largely unknown. We used 3‐ and 15‐mo‐old mice as well as 15‐mo‐old mice treated with vehicle and gefitinib to evaluate structural, cellular, and molecular changes in cortical bone. We found that the senescence of osteoprogenitors was increased, whereas the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…This hypothesis is further strengthened by the short time from the diagnosis of BM to the appearance of SRE (3.63 months) observed in our series and the greater distribution of these events in the first 12 months, a period in which the tumor is generally responsive to TKIs. Preclinical in vivo studies demonstrated that EGFR is essential for osteoblast proliferation (23) and down-regulated EGFR signaling was shown to favor the senescence of osteoprogenitors and the decline in bone formation on the endosteal surface of cortical bone (24). The administration of EGFR inhibitors, therefore, could impair the osteoblast mediated bone repair thus favoring the early occurrence of SREs despite the efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is further strengthened by the short time from the diagnosis of BM to the appearance of SRE (3.63 months) observed in our series and the greater distribution of these events in the first 12 months, a period in which the tumor is generally responsive to TKIs. Preclinical in vivo studies demonstrated that EGFR is essential for osteoblast proliferation (23) and down-regulated EGFR signaling was shown to favor the senescence of osteoprogenitors and the decline in bone formation on the endosteal surface of cortical bone (24). The administration of EGFR inhibitors, therefore, could impair the osteoblast mediated bone repair thus favoring the early occurrence of SREs despite the efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical in vivo studies demonstrated that EGFR is essential for osteoblast proliferation ( 23 ) and down-regulated EGFR signaling was shown to favor the senescence of osteoprogenitors and the decline in bone formation on the endosteal surface of cortical bone ( 24 ). The administration of EGFR inhibitors, therefore, could impair the osteoblast mediated bone repair thus favoring the early occurrence of SREs despite the efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signalling is critical for the survival, proliferation as well as differentiation osteoblastic cells (Liu et al, 2019; Zhang et al, 2011). Here our work shows a new role of EGFR signalling that it can mediate the internalisation of S. aureus by osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the over activation of epidermal growth factor receptor (EGFR) signalling in S. aureus ‐infected bone (Chen, Yao, et al, 2018; Mendoza Bertelli et al, 2016). Epidermal growth factor receptor (EGFR) is a key molecule regulating cell survival (Liu et al, 2019; Zhang et al, 2011). Crosstalk among EGFR, Src and FAK has been attributed to various cellular behaviours (Chen, Oh, et al, 2018; Pentassuglia & Sawyer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sesamin bound to the active pocket of vascular endothelial growth factor A (VEGFA). e920485-12 which the expression of p-EGFR on the endosteal surface of cortical bone was decreased in 15-month-old mice compared with that in 3-month-old mice [51]. This finding indicated that EGFR had a relationship with age in bone metabolism.…”
Section: E920485-11mentioning
confidence: 86%